Strategy to Improve Student’s Competence in Writing Opinion Article based on Enviromental Issues - Sarwiji Suwandi; Nugraheni Eko Wardani; Chafit Ulya (Fakultas Bahasa dan Seni UNP, 2020)
Natural disasters that have hit Indonesia recently have caused huge losses. Low public awareness about the importance of the environment as one of the causes. Therefore, the internalitation of environmental care attitudes and behavior is continuously carried out. One effort that can be done is through efforts to integrate ecological intelligence in Indonesian language learning, especially the skills to write opinion articles. This article aims to explain (1) the strategy of writing articles on environmental insight and (2) writing articles of environmental insight. The subjects of this study were teachers and high school students in Surakarta. The results that can be obtained from this study are as follows. First, the strategy to increase the competence of writing opinion articles based on environmental issues is achieved in stages, namely focus group discussions, workshops and training for teachers, learning to write opinion articles in class, assignments to students, reviewing student opinion works, and publication to mass media and collection books. student opinion work. Second, student competency in writing opinion articles about environmental issues have increased.